Reduction kinetics of hematite to magnetite under hydrothermal treatments. Issue 22 (11th March 2015) - Lu, J. F.; Tsai, C. J.
<x xml:space="preserve">Abstract</x> The phase transformation of α-Fe2O3 to Fe3O4 was observed by the hydrothermal treatment of a ferric solution at 160–220 °C with the addition of both KOH and EDA into the reaction system.